Bioakumulasi Timbal (Pb) pada Bivalvia (Anadara antiquata, Anadara granosa dan Perna viridis) dari Perairan Lekok, Pasuruan - Ulinuha, Devi; Perwira, Ima Yudha (Journal of Marine and Aquatic Sciences; Vol 8 No 2 (2022), 2022)
Lead is one of inorganic material causes pollution in waters that have a high level of toxicity for organisms. Lead pollution in waters can be accumulated by several water organisms, such as Bivalves. Bivalves are type of shellfish that can accumulate heavy metals. This study aimed to know the bioaccumulation of Lead on the Bivalves ( Anadara antiquata, Anadara granosa dan Perna viridis ) found in Lekok water (Pasuruan, Jawa Timur). The amount of Lead in the water, sediment and Bivalves was measured by using Atomic Absorption Spectro-photometer (AAS). The bioaccumulation of Lead on the Bivalves was analyzed by using Bioconcentration Factor (BCF). The result showed that amount of Lead in the water and sediment were 0,356 mg/L and 21,245 mg/kg, respectively. The BCF value of Lead on the Bivalves of Lekok waters were <30 indicating low accumulation level.